Characterization of Cellobiose Dehydrogenase (CDH) Enzyme in Trametes versicolor strain TRAMS - Munif, Tri Haidar; Rahmawan, Marjori Bethania; Abdulgani, Nurlita; Prasetyo, Endry Nugroho (Jurnal Biologi Tropis, 2025)
Cellobiose dehydrogenase (CDH, EC 1.1.99.18) is an enzyme classified under the oxidoreductase group. CDH has been widely utilized in various fields, including healthcare such as in wound dressing and in the energy sector for bioenergy production. To support these industrial applications, it is necessary to investigate the characteristics of CDH to enhance process efficiency. Therefore, this study aims to characterize CDH produced by the fungus Trametes versicolor strain TRAMS. The research involved constructing a CDH production curve followed by enzyme activity assays, protein content determination, isoelectric point (pI) analysis, and kinetic studies using Michaelis-Menten and Lineweaver-Burk plots. The results showed that the enzyme exhibited an activity of 3.441 U/mL on the 8th day of production. The enzyme's specific activity reached 61.57 U/mg at the 80% ammonium sulfate fraction, with an isoelectric point at pH 4. Enzyme kinetics based on the Michaelis-Menten plot revealed a Vmax of 6.7 µM/min and a Km of 3.35 µM, while the Lineweaver-Burk analysis indicated a Vmax of 9.625 µM/min and a Km of 0.23 µM.